Non-contact Health Monitoring to Support Care in a Psychiatric Intensive Care Unit. (1st September 2022) - Ndebele, Faith; Wright, Kay; Gandhi, Varsha; Bayley, Daniel
Objective: Psychiatric intensive care units provide care to patients with severe mental health disorders, often associated with violence and aggression which may result in the administration of rapid tranquillisation (RT). Novel technologies may support staff in monitoring patient safety and intervening proactively to prevent assaults and RT. The objective of this single-centre pragmatic study was to assess the effect of clinical teams augmenting their existing clinical practices with a contact-free vision-based patient monitoring system on the number of assaults and RT events. Method: The number of incidents of assaults, and the associated use of RT, was examined before and after the introduction of a contact-free vision-based patient monitoring system in a male psychiatric intensive care unit. Staff surveys and interviews were undertaken to assess usability and acceptability of the system. Results: There was a 37% reduction in assaults across the wards with 26% reduction in bedroom assaults. There was a 40% reduction in RT episodes related to assaults. Staff reported that they felt confident in monitoring the physical signs and health of patients remotely with the contact-free vision-based patient monitoring system to support them. Conclusion: The results suggest that the contact-free vision-based patient monitoring system helped staff to reduce incidents of assaults and associated RT administration. Staff surveys and interviews showed the ways in which their use of this technology had supported them in physical health monitoring.